Robust electromagnetic absorption by graphene/polymer heterostructures. (26th June 2015) - Lobet, Michaël; Reckinger, Nicolas; Henrard, Luc; Lambin, Philippe
Abstract: Polymer/graphene heterostructures present good shielding efficiency against GHz electromagnetic perturbations. Theory and experiments demonstrate that there is an optimum number of graphene planes, separated by thin polymer spacers, leading to maximum absorption for millimeter waves Batrakov et al (2014 Sci. Rep. 4 7191 ). Here, electrodynamics of ideal polymer/graphene multilayered material is first approached with a well-adapted continued-fraction formalism. In a second stage, rigorous coupled wave analysis is used to account for the presence of defects in graphene that are typical of samples produced by chemical vapor deposition, namely microscopic holes, microscopic dots (embryos of a second layer) and grain boundaries. It is shown that the optimum absorbance of graphene/polymer multilayers does not weaken to the first order in defect concentration. This finding testifies to the robustness of the shielding efficiency of the proposed absorption device.